Hepatocellular Carcinoma in an Adult with Repaired Tetralogy of Fallot. (16th August 2012) - McCabe, Nancy; Farris, Alton Brad; Hon, Huiming; Ford, Ryan; Book, Wendy M.
Abstract: Liver fibrosis is a growing concern among adults with congenital heart disease, particularly for those who have undergone a Fontan operation. Liver fibrosis leads to cirrhosis, a precursor of hepatocellular carcinoma. A few cases of hepatocellular carcinoma in patients with prior palliative surgery for congenital heart disease have been identified in the literature. The current case reports the first known case of hepatocellular carcinoma in a 45‐year‐old male with repaired tetralogy of Fallot.